MC4R Variant rs17782313 Associates With Increased Levels of DNAJC27, Ghrelin, and Visfatin and Correlates With Obesity and Hypertension in a Kuwaiti Cohort - Hammad, Maha M.; Abu-Farha, Mohamed; Hebbar, Prashantha; Cherian, Preethi; Al Khairi, Irina; Melhem, Motasem; Alkayal, Fadi; Alsmadi, Osama; Thanaraj, Thangavel Alphonse; Al-Mulla, Fahd; Abubaker, Jehad (Frontiers in Endocrinology, 2020)
Melanocortin 4 receptor (MC4R), a notable component of the melanocortin system, regulates appetite, body weight, and energy homeostasis. Genome-wide association studies have identified several MC4R variants associated with adiposity; of these, rs17782313, which is associated with increased body mass index (BMI) and overeating behavior, is of particular interest. Another gene associated with increased adiposity in global genome-wide association studies is DNAJC27, a heat shock protein known to be elevated in obesity. The detailed mechanisms underlying the role of MC4R variants in the biological pathways underlying metabolic disorders are not well understood. To address this, we assessed variations of rs17782313 in a cohort of 282 Arab individuals from Kuwait, who are deeply phenotyped for anthropometric and metabolic traits and various biomarkers, including DNAJC27. Association tests showed that the rs17782313_C allele was associated with BMI and DNAJC27 levels. Increased levels of DNAJC27 reduced the MC4R-mediated formation of cAMP. In conclusion, this study demonstrated an association between the rs17782313 variant near MC4R and increased BMI and DNAJC27 levels and established a link between increased DNAJC27 levels and lower cAMP levels. We propose that regulation of MC4R activity by DNAJC27 enhances appetite through its effect on cAMP, thereby regulating obesity.